Acute psychosis and serotonin syndrome in the setting of “Triple-C” overdose: a case report - Roudi Bachar (BMC, 2021)
Abstract Background Over-the-counter medication overdose is a difficult diagnostic challenge for many physicians as common drug screening assays cannot detect these substances. We present a case of acute psychosis, serotonin syndrome, and anticholinergic overdose-like properties in the setting of Coricidin HBP Cough & Cold tablets, known by their street name Triple-C. This is the first case report we are aware of involving a patient presenting with these symptoms and requiring critical-care-level support. Case presentation A 31-year-old African American female with a past medical history of anxiety, childhood asthma, previous methamphetamine abuse, and coronavirus disease 2019 infection in August 2020 was brought to the emergency department by the local police department with altered mental status. Initial blood work, including extended drug screens, were unremarkable for a definitive diagnosis. This patient required critical-care-level support and high sedation because of her symptoms. Collateral history revealed the patient regularly consumed Triple-C daily for the 6 weeks prior to admission. A trial off sedation was attempted after 24 hours with no complications. The patient admitted to regular Triple-C consumption and auditory hallucinations since adolescence. She was discharged safely after 48 hours back into the community. She was lost to follow-up with psychiatry and internal medicine; however, she was evaluated in the emergency room 1 month later with a similar psychiatric presentation. Conclusion Overdose of Triple-C should be kept in the differential diagnosis of patients presenting with a triad of psychosis, serotonin syndrome, and anticholinergic overdose, in the setting of unknown substance ingestion.